On Joan Didion: An Introduction. (1st September 2016) - Worden, Daniel; Young, Alex Trimble
ABSTRACT: Joan Didion is one of the most celebrated writers of our time. From her novels and reportage to her recent memoirs, Didion has honed a hallmark style and authorial persona, both of which have led to encomiums and controversy in the press. Yet when compared to American writers of similar notoriety, there are comparably few scholarly treatments of Didion's writings. In this multivoiced essay, scholars of life writing, documentary, and fiction explore the aesthetics and politics of Didion's work, as well as the ways in which Didion's many genres of writing—essay, memoir, novel, reportage—contribute to US politics, literary aesthetics, and the way we think of life writing today.